Studi Perbandingan Penambahan Palm Oil Fuel Ash (Pofa), Rice Husk Ash (Rha), dan Fly Ash (Fa) Terhadap Daya Serap Air dan Kuat Tekan Bata Ringan - Melati Panjaitan; M. Nuklirullah; Fetty Febriasti Bahar (GLOBAL SCIENTS PUBLISHER, 2026)
Cellular Lightweight Concrete (CLC) is a widely used construction material due to its lightweight properties, good thermal insulation, and ease of application. However, the high cement content required in CLC production contributes to increased carbon emissions and production costs. This study aims to analyze the effect of Palm Oil Fuel Ash (POFA), Rice Husk Ash (RHA), and Fly Ash (FA) as partial cement replacements on the water absorption and compressive strength of CLC lightweight bricks. The research employed a laboratory experimental method with a quantitative approach. Cement substitution levels of 5%, 7.5%, and 10% were applied for each type of ash. The tests included fine aggregate characterization, water absorption, and compressive strength in accordance with applicable standards. The results indicate that POFA, RHA, and FA have different effects on the properties of CLC lightweight bricks. Certain substitution levels improved compressive strength and reduced water absorption compared to normal CLC bricks, whereas excessive substitution tended to reduce mechanical performance due to the decreased amount of active cement. Therefore, POFA, RHA, and FA have significant potential as environmentally friendly supplementary cementitious materials for producing sustainable lightweight concrete with improved engineering properties.